Analysis of marсovian systems with a given set of selected states - Raskin, Lev; Sukhomlyn, Larysa; Korsun, Roman (Національний технічний університет "Харківський політехнічний інститут", 2022)
Analysis of stationary Marcovian systems is traditionally performed using systems of linear Kolmogorov differential equations. Such systems make it possible to determine the probability of the analyzed system being in each of its possible states at an arbitrary time. This standard task becomes more complicated if the set of possible states of systems is heterogeneous and some special subset can be distinguished from it, in accordance with the specifics of the system functioning. Subject of the study is technology development for such systems analysis. In accordance with this, the purpose of the work is to find the distribution law of the random duration of such a system's stay on a set of possible states until it falls into a selected subset of these states. Method for solving the problem is proposed based on splitting the entire set of possible states of the system into two subsets. The first of them contains a selected subset of states, and the second contains all the other states of the system. Now a subset of states is allocated from the second subset, from which a direct transition to the states of the first subset is possible. Next, a system of differential equations describing the transitions between the formed subsets is formed. The solution of this system of equations gives the desired result – distribution of the random duration of the system's stay until the moment of the first hit in the selected subset of states. The method allows solving a large number of practical problems, for example, in the theory of complex systems reliability with many different failure states. In particular, finding the law of the uptime duration distribution, calculating the average duration of uptime.

Аналіз стаціонарних марківських систем зазвичай виконується з допомогою систем лінійних диференціальних рівнянь Колмогорова. Такі системи дозволяють визначити ймовірність перебування аналізованої системи у кожному з можливих станів у довільний момент часу. Ця стандартна задача ускладнюється, якщо множина можливих станів систем є неоднорідною і з неї можна виділити, відповідно до специфіки функціонування системи, певну особливу підмножину. Предмет дослідження полягає у розробці технології аналізу таких систем. Відповідно до цього мета роботи – відшукання закону розподілу випадкової тривалості перебування такий системи на множині можливих станів до моменту потрапляння у виділену підмножину цих станів. Запропоновано метод вирішення поставленої задачі, заснований на розбитті всієї множини можливих станів системи на дві підмножини. Перша містить виділену підмножину станів, а друга – решта станів системи. Тепер із другої підмножини виділяється субпідмножина станів, з яких можливий безпосередній перехід у стани першої підмножини. Далі формується система диференціальних рівнянь, що описують переходи між сформованими підмножинами. Розв'язання цієї системи рівнянь дає шуканий результат – розподіл випадкової тривалості перебування системи до моменту першого потрапляння у виділену підмножину станів. Метод дозволяє вирішувати велику кількість практичних завдань, наприклад, у теорії надійності складних систем з безліччю різних відмовних станів. Зокрема, знаходження закону розподілу тривалості безвідмовної роботи, розрахунок середньої тривалості безвідмовної роботи.
Аналіз марківських систем із заданою множиною виділених станів
Keywords: Marcovian systems; subset of special states; analysis of inhomogeneous systems states probabilities dynamics; марківські системи; підмножина особливих станів; аналіз динаміки ймовірностей станів неоднорідних систем